Preclinical Models of Encephalopathy of Prematurity - Jantzie, Lauren L. (Dev Neurosci, 2015)
Encephalopathy of prematurity (EoP) encompasses the central nervous system (CNS) abnormalities associated with injury from preterm birth. Although rapid progress is being made, limited understanding exists of how the cellular and molecular CNS injury from early birth manifests as the myriad of neurological deficits in children who are born preterm. More importantly, this lack of direct insight into the pathogenesis of these deficits hinders both our ability to diagnose those infants who are at risk in real-time and could potentially benefit from treatment, and our ability to develop more effective interventions. Current barriers to clarifying the pathophysiology, developmental trajectory, injury timing and evolution include preclinical animal models that only partially recapitulate the molecular, cellular, histological and functional abnormalities observed in the mature CNS following EoP. Inflammation from hypoxic-ischemic and/or infectious injury induced in utero in lower mammals, or actual prenatal delivery of more phylogenetically-advanced mammals, are likely to be the most clinically relevant EOP models, facilitating translation to benefit infants. Injury timing, type, severity and pathophysiology need to be optimized to address the specific hypothesis being tested. Functional assays of the mature animal following perinatal injury to mimic EoP should ideally test for the array of neurological deficits commonly observed in preterm infants including gait, seizure threshold, cognitive and behavioral abnormalities. Here, we review the merits of various preclinical models, identify gaps in knowledge that warrant further study and consider challenges that animal researchers may face in embarking on these studies. While no one model system is perfect, insights relevant to the clinical problem can be gained with interpretation of experimental results within the context of inherent limitations of the chosen model system. Collectively, optimal use of multiple models will address a major challenge facing the field today – to identify the type and severity of CNS injury these vulnerable infants suffer in a safe and timely manner, such that emerging neuro-interventions can be tailored to specifically address individual reparative needs.